PENGARUH PROMOSI DAN KEMUDAHAN PENGGUNAAN TERHADAP LOYALITAS PELANGGAN PADA LAYANAN SHOPEEFOOD DI JAKARTA - Ranti Putri Pratiwi; Angga Putri Ekanova; Olivia Puspita Nagari (Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the effect of promotion and ease of use partially and simultaneously on customer loyalty at shopeefood service in Jakarta. The analytical method in this study uses quantitative primary data, the stages carried out are: data quality test, classical assumption test, multiple linear regression analysis, t test (partial), f test (simultaneous), coefficient of determination (R2) using tools spss testing. The data used in this study were obtained by distributing questionnaires to 100 respondents. The results of this study indicate that the promotion variable can partially and significantly affect customer loyalty at Shopeefood services in Jakarta. The ease of use variable partially and significantly can effect customer loyalty at ShopeeFood services in Jakarta. There is a simultaneous and significant influence between the variables of promotion and ease of use on customer loyalty at ShopeeFood service in Jakarta.